Nup98 Is a Mobile Nucleoporin with Transcription-dependent Dynamics - Eric R. Griffis; Nihal Altan; Jennifer Lippincott‐Schwartz; Maureen A. Powers (2002)
Nucleoporin 98 (Nup98), a glycine-leucine-phenylalanine-glycine (GLFG) amino acid repeat-containing nucleoporin, plays a critical part in nuclear trafficking. Injection of antibodies to Nup98 into the nucleus blocks the export of most RNAs. Nup98 contains binding sites for several transport factors; however, the mechanism by which this nucleoporin functions has remained unclear. Multiple subcellular localizations have been suggested for Nup98. Here we show that Nup98 is indeed found both at the nuclear pore complex and within the nucleus. Inside the nucleus, Nup98 associates with a novel nuclear structure that we term the GLFG body because the GLFG domain of Nup98 is required for targeting to this structure. Photobleaching of green fluorescent protein-Nup98 in living cells reveals that Nup98 is mobile and moves between these different localizations. The rate of recovery after photobleaching indicates that Nup98 interacts with other, less mobile, components in the nucleoplasm. Strikingly, given the previous link to nuclear export, the mobility of Nup98 within the nucleus and at the pore is dependent on ongoing transcription by RNA polymerases I and II. These data give rise to a model in which Nup98 aids in direction of RNAs to the nuclear pore and provide the first potential mechanism for the role of a mobile nucleoporin.